Physical Measurement Analysis in Pre-Utility Covid-19 Isolation Room: A Case Study Universitas Mataram Teaching Hospital - Eustachius Hagni Wardoyo; Ida Bagus Alit; Monalisa Nasrul; Didit Yudhanto; Prima Belia Fathana; Rini Srikus Saptaningtyas (The Indonesian Journal of Infectious Diseases, 2021)
Background: Negative pressure room is recommended for the treatment of COVID-19 patients. Aim this study to describe physical measurement analysis of isolation room Universitas Mataram Teaching Hospital. Methods: Newly developed negative pressure isolation room was physical measure using following instruments: anemometer, moisture meter, hygrometer and pressure gauge.  Results: This study showed physical measurement as follow: 1) ACH (air change per hour) 23.3 / hour [minimum: 12+ ACH]; 2) the difference in pressure gradient between the inpatient room and anteroom -30 Pa [minimum -15 Pa]; 3) the mean of air temperature 24.8°C [21-24]; 4) air humidity 58% [maximum 65%] and 5) concrete moisture 22.45%. Conclusion: The COVID-19 isolation room at the Universitas Mataram Teaching Hospital meets the standard criteria.